2021
DOI: 10.1186/s12884-021-04105-9
|View full text |Cite
|
Sign up to set email alerts
|

The successful implementation of the Enhanced Recovery After Surgery (ERAS) program among caesarean deliveries in Bhutan to reduce the postoperative length of hospital stay

Abstract: Background Enhanced Recovery After Surgery (ERAS) is a multidisciplinary perioperative care program to optimize and enhance postoperative recovery. It has a beneficial role in decreasing the length of hospital stay and improving the quality of care. This study aims to observe the successful implementation of ERAS in reducing the length of hospital stay (LOS) among caesarean deliveries. Methods A pre-and post-implementation study of ERAS protocol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
5
12
0
2
Order By: Relevance
“…After 2015, patient-reported outcomes were the purpose of ERAS. More attention has been paid to the comfort and safety of patients in hospitals, as well as the reduction of surgical complications, rather than the reduction of hospital days and cost alone (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…After 2015, patient-reported outcomes were the purpose of ERAS. More attention has been paid to the comfort and safety of patients in hospitals, as well as the reduction of surgical complications, rather than the reduction of hospital days and cost alone (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 36 LOS remains the most popular outcome measure, most frequently reported in days. LOS was reduced in the ERAC group in most studies, 12 , 13 , 15 , 16 , 18 , 19 , 20 , 22 , 24 , 25 , 27 , 28 , 37 but unchanged in the rest. 14 , 17 , 21 , 23 , 29 Other process metrics include proportion of patients discharged on days 1 and 2, ERAC pathway compliance, and time to achieving interim clinical milestones such as first mobilization and urinary catheter removal.…”
Section: Introductionmentioning
confidence: 91%
“…The major disadvantages of process metrics in healthcare are that they do not measure patient experience and clinical outcome, which could be poor despite efficient processes, and do not necessarily translate to good clinical safety and quality. Of the 22 studies, only 1 reported reduced maternal readmission rates, 25 whereas 12 found no increase, 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 28 , 30 , 37 and the remaining 9 studies did not report this outcome. 15 , 16 , 23 , 24 , 27 , 29 , 35 , 36 , 37 One RCT showed a reduction in readmission rates associated with ERAC implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations